2015
DOI: 10.1260/2041-4196.6.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Impact Resistance and Failure Analysis of Plain Woven Curtains

Abstract: Blast and impact-resistant curtains are increasingly utilized for various applications in critical infrastructures to retrofit or enhance energy absorption and fragments capturing capabilities. Investigation of the impact resistance and failure mechanisms of the protective curtains are therefore critical. Understanding the energy absorption and failure mechanisms of fabrics impacted by potential debris of medium to low striking speeds could thus lead to improvements in designing spall linings system as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Such model could be, however, computational intensive to simulate the multilayer systems. Several analytical, numerical and hybrid approaches [18][19][20][21][22] have been explored to model the ballistic impacts of woven fabrics. Numerical models at different scales were developed, including the macro-scale that simulates fabric layer as homogenised membranes, the mesoscale that constructs the fabrics from anisotropic continuum yarn, and the microscale focusing on the fibre level [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Such model could be, however, computational intensive to simulate the multilayer systems. Several analytical, numerical and hybrid approaches [18][19][20][21][22] have been explored to model the ballistic impacts of woven fabrics. Numerical models at different scales were developed, including the macro-scale that simulates fabric layer as homogenised membranes, the mesoscale that constructs the fabrics from anisotropic continuum yarn, and the microscale focusing on the fibre level [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…High strength PES fibers are generally preferred. Experimental and FE numerical investigations were carried out by several researchers, in the last years, to explore the potential and feasibility of these textile curtains, so that they could be efficiently used as a passive protection device for glass facades, see [88][89][90][91][92][93]. Careful consideration was spent, in [89,91], for the assessment of major effects and failure process of woven fabric drapes (Twaron® plain weave samples), under ballistic impact (0.22 calibre bullet projectiles with spherical For example, several non-woven technologies can be used for blast-resistant curtains [87].…”
Section: Textiles Forprotective Claddings and Blast Proof Curtainsmentioning
confidence: 99%
“…Researchers have demonstrated that auxetic foams show higher strength to weight ratio, lower stiffness and better energy absorption than conventional ones [25,38,39,40,41,42]. In addition, sandwich panels with auxetic cores; have been investigated under static and blast-induced dynamic shockwaves.…”
Section: Introductionmentioning
confidence: 99%